Spatial and geographic analysis of eolic potential in Colombia: Análisis espacial y geográfico del potencial eólico en Colombia - Albadan Molano, David Esteban; Salas Pérez, Cristian; Coy Castro, Daniel Felipe (Noria Investigación Educativa, 2019)
The following study focuses on a spatial analysis of the Colombian territory with Geographic Information Systems (GIS) tools, determining probabilistically the key points with the highest wind energy potential, using a fitted probability distribution function (PBDF), this information was captured along 10 years, by meteorological stations of the Institute of Hydrology, Meteorology and Environmental Studies (IDEAM), installed in a large part of the country. The wind velocity and density data were used to generate the cartography records for the identification of the areas of the country with the most wind potential, locating the areas of the country with high energy potential such as the region of La Guajira and Nudo de Los Pastos. This study provides an estimation of the wind energy capacity of Colombia, arriving to the conclusion that due to its geographical characteristics the country could be able to satisfy its energy demand with the use of wind turbines.